2018
DOI: 10.5897/jvmah2017.0639
|View full text |Cite
|
Sign up to set email alerts
|

Review of common causes of abortion in dairy cattle in Ethiopia

Abstract: Abortion in dairy cattle may be caused by infectious and non-infectious agents. Infectious causes of abortion in dairy cattle include brucellosis, leptospirosis, listeriosis, Q fever, bovine viral diarrhea, mycotic abortion and neosporosis. Non-infectious causes of abortion in dairy cattle are genetic and non-genetic disorder. Risk factors associated with abortion in dairy cattle are genetic, environmental, management, geographical factors and infectious factors. Abortion in dairy cows brings about breeding an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 79 publications
1
10
0
3
Order By: Relevance
“…16 In addition, abortion usually caused by brucellosis and leptospirosis occurs in the third trimester. 5,11,46 This is in agreement with previous studies in Ethiopia 8,36,37,47 and elsewhere, 48 which reported that most of the abortion cases occurred in the third trimester. This result is different from the reports of Thurmond et al 18 and Hanson et al, 49 who reported that the highest risk of abortion occurred in the second trimester.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…16 In addition, abortion usually caused by brucellosis and leptospirosis occurs in the third trimester. 5,11,46 This is in agreement with previous studies in Ethiopia 8,36,37,47 and elsewhere, 48 which reported that most of the abortion cases occurred in the third trimester. This result is different from the reports of Thurmond et al 18 and Hanson et al, 49 who reported that the highest risk of abortion occurred in the second trimester.…”
Section: Discussionsupporting
confidence: 90%
“…4 Ethiopia has given priority on the improvement of dairying at farmer level to extend the provision of milk from smallholder dairy farms. 5,6 However, reproductive disorder has become a major obstacle to this development plan. Among these, abortion was the main constraint for this development to achieve its goal.…”
Section: Introductionmentioning
confidence: 99%
“…Pada kawin alam di kandang kelompok "Model Litbangtan" eksistensi pejantan unggul yang mampu mengawini sejumlah ekor induk dalam kurun waktu tertentu Beberapa hasil penelitian menunjukkan bahwa abortus dialami oleh sapi pada umur kebuntingan diatas 5 (lima) bulan [23]. Penyebabnya bisa dari faktor non genetik seperti lingkungan, manajemen, ketidakstabilan hormon maupun ketidaksiapan uterus untuk bunting [24].…”
Section: Angka Kebuntingan Serta Fenomena Yang Terjadi Selama Kebuntiunclassified
“…Bakteri Brucella abortus merupakan salah satu bakteri yang menyebabkan keguguran pada ternak (Quinn et al, 2002;Dereje et al, 2018). Penyakit yang disebabkan oleh bakteri Brucella sp.…”
Section: ■ Pendahuluanunclassified